Tree growth at the limits: the response of multiple conifers to opposing climatic constraints along an elevational gradient in the Alps - Obojes, Nikolaus; Buscarini, Serena; Meurer, Armin Konrad; Tasser, Erich; Oberhuber, Walter; Mayr, Stefan; Tappeiner, Ulrike (Frontiers in Forests and Global Change, 2024)
Climate change affects the vitality of mountain forests through increasing temperatures as well as decreasing water availability due to changing precipitation patterns, earlier snow melt, and increasing evaporative demand. Depending on species characteristics, tree growth might therefore increase in cold habitats near the forest line but decrease in water-limited conditions at lower elevation. We analysed the tree-ring widths of five conifers (Picea abies, Larix decidua, Pinus sylvestris, Pinus nigra, and Pinus cembra) along an elevational gradient from 1000 m to 2320 m above sea level (a.s.l.) in Vinschgau/ Val Venosta Valley in Northern Italy, one of the driest regions of the Alps (mean annual precipitation 682 mm at 1310 m a.s.l.). Our aim was to estimate the speciesspecific growth response on changing climate conditions along an elevational gradient. At low elevations, we observed a significant response to water availability not only during the actual growing season but also throughout the previous autumn for all species present. At mid-elevation, the correlation coefficients to precipitation and drought indices (SPEI) were highest for Picea abies.At high elevations, the positive correlation of growth with temperature was smaller than expected for Pinus cembra. In contrast, Larix decidua responded positively to temperature and grew faster in recent decades. Considering that a further increase in temperatures will reduce plant water availability during the growing season, our space-for-time approach provides an outlook on future growth conditions of conifers in larger regions of the European Alps. Water limitation will affect tree growth and vitality not only at low elevations in the valleys but also at mid elevation on mountain slopes, potentially impacting timber production as well as the protective and recreative functions of forests. Near the forest line, the different capability of tree species to benefit from higher temperatures might lead to changes in species composition.